Aktifitas Antioksidan dan Sensori Herbal Kunyit Asam Lemon Cui - Laboko, Asriani; Zainuddin, Asniwati; Karim, Agung Prasetyo; Lamiun, Noviyani; Pade, Satriawati; Fitriani, Andi Nur (Program Studi Teknologi Hasil Pertanian Fakultas Sains dan Teknologi Hasil Pertanian Universitas Muhammadiyah Sidenreng Rappang, 2025)
This research aims to determine the antioxidant activity and consumer preference levels for an herbal drink made from turmeric, tamarind, and lemon (Cui) through sensory evaluation. Additionally, the study seeks to assess the quality of the instant turmeric, tamarind, and lemon drink as a functional beverage. The study was conducted using an experimental method with a Completely Randomized Design (CRD), consisting of one factor and three replications. The parameters observed included antioxidant activity, sugar content, and sensory attributes such as taste, aroma, and color. The results indicated that the highest antioxidant activity categorized as very strong was found in treatments H1 and H2, both with a value of 0.24 ppm. The sugar content that aligns with industry standards is approximately 7%; the closest value was observed in treatment H1, with a sugar content of 11.82%. Based on sensory evaluations conducted by 30 panelists, treatment H1 received the highest preference score in terms of taste.